1997
DOI: 10.1111/j.1745-6584.1997.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Ground‐Water Flow Systems in the Southern Great Basin Using Aqueous Rare Earth Element Distributions

Abstract: The rare earth element (REE) signature of ground waters from both felsic volcanic rocks on the Nevada Test Site and from the regional Paleozoic carbonate aquifer of southern Nevada resemble the REE signature of the rocks through which they flow. Moreover, the REE signatures of Ash Meadows ground waters are similar to those of springs in the Furnace Creek region of Death Valley but different from shallow ground waters from predominantly tuffaceous alluvial deposits in the Amargosa Desert, perched ground waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Johannesson et al (1997) point out that the water discharging at Furnace Creek and Ash Meadows springs have similar REE signatures, whereas water from wells in the Amargosa Desert basin-fill aquifer is quite different. Johannesson et al (1997) conclude that, based on REE data, the primary component of water discharging at Furnace Creek springs appears to be through-flow Ash Meadows groundwater, which may or may not contain a smaller component of shallow basin-fill ground-water from the Amargosa Desert. This work supports the theory of ground-water flow through the frac-tured carbonate rocks beneath Ash Meadows and the southern Funeral Mountains.…”
Section: Geochemical Controls On Ground-water Flow To Furnace Creek Smentioning
confidence: 98%
See 2 more Smart Citations
“…Johannesson et al (1997) point out that the water discharging at Furnace Creek and Ash Meadows springs have similar REE signatures, whereas water from wells in the Amargosa Desert basin-fill aquifer is quite different. Johannesson et al (1997) conclude that, based on REE data, the primary component of water discharging at Furnace Creek springs appears to be through-flow Ash Meadows groundwater, which may or may not contain a smaller component of shallow basin-fill ground-water from the Amargosa Desert. This work supports the theory of ground-water flow through the frac-tured carbonate rocks beneath Ash Meadows and the southern Funeral Mountains.…”
Section: Geochemical Controls On Ground-water Flow To Furnace Creek Smentioning
confidence: 98%
“…Studies have shown that ground-water and some surface waters can inherit their REE signatures from the rock through which the water has flowed (Smedley, 1991;Fee et al, 1992). Johannesson et al (1997) used REE signatures to evaluate ground-water flow-paths and mixing in the carbonate aquifer of southern Nevada. Johannesson et al (1997) point out that the water discharging at Furnace Creek and Ash Meadows springs have similar REE signatures, whereas water from wells in the Amargosa Desert basin-fill aquifer is quite different.…”
Section: Geochemical Controls On Ground-water Flow To Furnace Creek Smentioning
confidence: 99%
See 1 more Smart Citation
“…The general consensus is that reducing groundwater impedes the movement of most trace elements, including their radioactive isotopes, and oxidizing conditions favor such movement. Water from springs in the Ash Meadows National Wildlife Refuge, located about 60 miles to the northwest of Las Vegas and about 25 miles south of Yucca Mountain, is thought to consist of water originating on the eastern side of the NTS (the Pahranagat Valley) along with recharge from the nearby Spring Mountains, just east of Ash Meadows [38]. It is not known if any component of this water originates from the NTS.…”
Section: Vanadium Speciation In Southern Nevada Groundwatermentioning
confidence: 99%
“…The methods used to measure the REEs were described previously by Johannesson et al (1996Johannesson et al ( , 1997a and will only be summarized below. The following REE isotopes were monitored during analysis and used to quantify REE concentrations in the groundwaters because they are free of elemental isobaric interferences: 139 (Johannesson and Lyons, 1994;Johannesson et al, 1997a). All oxide interferences by other REEs were corrected for during analysis.…”
Section: Sampling and Analytical Techniquesmentioning
confidence: 99%